W. A. Scott papers - Scott, W. A. (William Anderson), 1813-1885.
Two letters (1842 June 16 and 1845 February 13) written by Andrew Jackson to Scott; letter (undated) written by Scott's wife, Anna Nicholson Scott, to Gen. Horatio Gouverneur Wright; letter (1879 November 14) written by William G. Mitchell to Winfield Scott Hancock relating to Mary E. Surratt; and notes (1949 and 1963) of James Scott Baker relating to the Mitchell and Anna Nicholson Scott letters.
Handwritten and typewritten transcripts.
Negative photocopies made with the permission of James Scott Baker.
Presbyterian clergyman and educator.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Baker, James Scott; Hancock, Winfield Scott, -- 1824-1886 -- Correspondence; Jackson, Andrew, -- 1767-1845 -- Correspondence; Mitchell, William G. -- Correspondence; Scott, Anna Nicholson, -- 1811-1888 -- Correspondence; Surratt, Mary E. -- 1820-1865.; Wright, Horatio Gouverneur, -- 1820-1899 -- Correspondence; Presbyterian Church -- Clergy; Clergy; Educators